THE INFLUENCE OF STOCKING DENSITIES ON WHITE SHRIMP (Litopenaeus vannamei) REARED USING INTENSIVE SYSTEM: PRODUCTION PERFORMANCE AND WATER QUALITY - Insani, Liga; Jatayu, Diklawati; Mahendra, I Gede Rezza; Wiyasa, Made Wisnu; Kurnianto, Bayu; Ardiansyah, Ardiansyah (Jurnal Perikanan Unram, 2025)
ABSTRACT The increasing trend of vaname shrimp cultivation production encourages farmers to increase their cultivation production. The success of vaname shrimp cultivation can be seen from the ability to measure the capacity of shrimp biomass in maintenance activities and stocking density patterns based on the maximum capacity of the pond in each plot. The purpose of this study was to analyze vaname shrimp cultivation activities for a period of 2 years (2023-2024) in intensive system ponds based on different stocking density patterns at 140 shrimp/m2 and 190 shrimp/m2. This study was carried out for 6 cultivation cycles, each cycle was carried out for 100 days. The results of statistical tests showed that the shrimp stocking density pattern had a significant effect (p <0.05) on biomass, productivity, survival and feed conversion ratio. The average survival rate of 140 shrimp/m2 stocking density was 85.33%, biomass was 3,327.75 kg, FCR was 1.44 and productivity was 30.8 tons/ha. The average survival rate with a stocking density of 190 shrimp/m2 was 73.66%, biomass 1,981.87 kg, FCR 1.59 and productivity 12.38 tons/ha. This shows that biomass, SR, and productivity decreased while FCR tended to increase in cultivation with a stocking density of 190 shrimp/m2. The results of water quality showed an increase in the Total Organic Matter value of 110-250 mg/l at a stocking of 190 shrimp/m2. This shows that there is an increase in organic matter in the maintenance pond which affects the survival of shrimp in the pond so that it affects the biomass and productivity of whiteleg shrimp. A stocking density of 140 shrimp/m2 can be recommended for application in intensive whiteleg shrimp cultivation. Keywords: intensive system, stocking density, water quality, whiteleg shrimp